2018
DOI: 10.1007/s10924-018-1300-x
|View full text |Cite
|
Sign up to set email alerts
|

A Solvent-Free Approach for Production of Films from Pectin and Fungal Biomass

Abstract: Self-binding ability of the pectin molecules was used to produce pectin films using the compression molding technique, as an alternative method to the high energy-demanding and solvent-using casting technique. Moreover, incorporation of fungal biomass and its effects on the properties of the films was studied. Pectin powder plasticized with 30% glycerol was subjected to heat compression molding (120 °C, 1.33 MPa, 10 min) yielding pectin films with tensile strength and elongation at break of 15.7 MPa and 5.5%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The lower the value, the higher is the resistance to water vapor. The water vapor permeability of bio-based films prepared in the optimization experiment, regardless of preparation method, had a mean value of 1.19 (± 0.08) × 10 −13 kg/m Pa s, which can be compared with the WVP of fungal biomass-reinforced pectin films of 2.35 × 10 −13 kg/m Pa s [28] and edible films from alginate-acerola reinforced with cellulose whiskers of 1.67 (± 0.42) × 10 −13 kg/m Pa s [29]. Both of these studies reported lower WVP values when the reinforcement load increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower the value, the higher is the resistance to water vapor. The water vapor permeability of bio-based films prepared in the optimization experiment, regardless of preparation method, had a mean value of 1.19 (± 0.08) × 10 −13 kg/m Pa s, which can be compared with the WVP of fungal biomass-reinforced pectin films of 2.35 × 10 −13 kg/m Pa s [28] and edible films from alginate-acerola reinforced with cellulose whiskers of 1.67 (± 0.42) × 10 −13 kg/m Pa s [29]. Both of these studies reported lower WVP values when the reinforcement load increased.…”
Section: Resultsmentioning
confidence: 99%
“…Both of these studies reported lower WVP values when the reinforcement load increased. The lowest value was obtained when fungal biomass load was 35 wt % [28] and when cotton cellulose whiskers were used at 15 wt % [29].…”
Section: Resultsmentioning
confidence: 99%
“…Compression molding technique has been widely employed for the development of biofilms or 3D objects without the use of any solvent or binder [ 88 , 102 ]. With this technique, the waste of interest or its dried extract is finely powdered and subjected to high temperatures and pressures through a heated press.…”
Section: Food Waste As Feedstock For Bioplastic Productionmentioning
confidence: 99%
“…Under this thermo-mechanical treatment, proteins undergo denaturation and dissociation leading to the formation of new links and their aggregation to new forms; in addition, biopolymers show a self-binding ability that is exploited to produce three-dimensional objects. Furthermore, the molding method is more suitable for industrial applications since it is characterized by lower energy demand and processing time compared to other techniques like solution casting [ 102 ].…”
Section: Food Waste As Feedstock For Bioplastic Productionmentioning
confidence: 99%
“…The material is used as animal feed but, because of its abundance and low nutritional value, it is sold inexpensively [8,9]. Alternatively, one can take advantage of the polymeric nature of both straw and bran and use them for the production of bio-based materials by heat compression molding, a technique involving the thermo-mechanical processing of a material [10].…”
Section: Introductionmentioning
confidence: 99%